Analysis of diagnosis delay among migrant pulmonary tuberculosis patients in Guangzhou from 2014 to 2022 - Yajuan Feng; Keng Lai; Jieying Yang; Yu Lei; Guifeng Wu; Yuhua Du; Weiyun He (Frontiers in Public Health)
BackgroundDelays in diagnosing pulmonary tuberculosis (PTB) lead to more severe disease progression and sustained transmission within communities. This study aimed to assess trends and identify risk factors associated with PTB diagnosis delays, especially among migrants, in Guangzhou from 2014 to 2022.MethodsDemographic and clinical information of PTB patients from 2014 to 2022 in Guangzhou were extracted from the PTB Information Management System (TBIMS). Diagnosis delays were categorized as patient delay (>30 days from symptoms onset to first care-seeking) and hospital delay (>14 days from first care-seeking to TB diagnosis). Multivariable logistic regression was used to analyze the risk factors for these delays.ResultsA total of 35,722 migrant PTB patients were registered in Guangzhou during the study period, exhibiting distinct characteristics compared to local residents (n = 44,155). The bacteriological positivity rate among migrants was significantly lower than that of the local residents (47.68% vs. 52.41%, p < 0.001). Overall, 44.39% patients experienced a diagnosis delay, comprising 27.90% with patient delay and 29.09% with hospital delay, with both showing a gradually declining trend over time. Multivariate logistic regression analysis revealed risk factors for diagnosis delay including female sex, older age, ethnic minority status, migrant status and re-treated patients, which were similar to patient delay. Risk factors for hospital delay included, passive case finding, and re-treated patients. Notably, sputum smear-positivity was positively associated with both the diagnostic delay (aOR 1.279, 95% CI: 1.224–1.335) and patient delay (aOR 1.642, 95% CI: 1.563–1.724), but reduced the risk of hospital delay (aOR 0.906, 95% CI: 0.866–0.950).ConclusionPublic health strategies should prioritize improving bacteriological detection rates among migrants, with targeted efforts for high-risk groups such as females, the older adult, and ethnic minorities.